Nordic labour market models in open markets - Andersen, Søren Kaj; Dølvik, Jon Erik; Lyhne Ibsen, Christian (Brussels, 2014)
"This report reviews the main common traits and variations of the Nordic models of labour market regulation, how they were adjusted after the crises in the 1980-90s, and how recent labour market developments have faced the actors with new challenges. The Nordic labour markets are still marked by comparatively strong, encompassing unions and employer organizations, multilevel bargaining systems, and broad coordination of wage setting at sectoral or peak level, but declining union density, especially at the lower ends of the labour market, combined with growing low-wage competition and cross-border work, raise questions about the unions’ ability to maintain collective agreement coverage and stem erosion of their local power bases. With higher unemployment in the wake of the crisis, easier exit opportunities for employers, and widening downward inequalities, the Nordic unions face diffi cult choices over how to bolster national wage fl oors. Views vary on whether they are still strong enough to rely solely on collective bargaining or whether they will need more state support to enforce and extend collective minimum wages to the sprawling fl ora of unorganized fi rms. While the latter view is adopted by Finnish, Icelandic and many Norwegian unions, the former view predominates among Danish and Swedish unions, and it remains to be seen how keen the employers’ associations and the politicians will be to support union calls for shoring up the system."